A retrospective study on the evaluation of the symptoms, medications and improvement of the quality of life of patients undergoing robotic surgery for gastroesophageal reflux disease - Konstantinidou, Sofia K. (Exp Ther Med, 2021)
Gastroesophageal reflux disease (GERD) is a common gastrointestinal disorder requiring lifestyle adaptations and administration of medications. Another approach is the surgical treatment of GERD through laparoscopic or robotic operations. The aim of the present study was to investigate the improvement of symptoms and quality of life of patients with GERD, before and after robotic surgical restoration using the Nissen robotic fundoplication technique. The potential effects of body weight, age and sex, as well as the response to medications and progress over time, were also assessed. A retrospective study was conducted in a tertiary hospital between October 2019 and March 2020. Data were collected and recorded from 144 patients who underwent robotic surgery, using the Nissen fundoplication technique, during the period 2009-2019. All patients involved in this analysis pre-operatively exhibited severe symptoms of heartburn and reflux, as well as poor quality of life. All of these symptoms were re-examined after surgery, and a marked decrease was observed with respect to their frequency and intensity. Improvement was not affected by body mass index, whereas older patients exhibited greater improvement. Women initially experienced more severe symptoms before the surgery, but they appeared to respond as well as the male patients. The long-term beneficial effects of surgery for up to the 10-year period studied were validated. After the robotic surgical rehabilitation, the vast majority of patients overcame the unpleasant symptoms of GERD and stayed off their medications. More than 4/5 of the patients were satisfied after surgery. In conclusion, restoration of GERD, using Nissen robotic fundoplication, led to the minimization of symptoms and to a marked improvement in the quality of life of patients.